IMPLEMENTASI CORE TAX ADMINISTRATION SYSTEM SEBAGAI UPAYA MENDORONG KEPATUHAN WAJIB PAJAK UMKM - M, RINTO RAHMAD (Fakultas Ekonomi Universitas Islam Indragiri, 2025)
This study aims to analyze the implementation of the coretax application in improving tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Using a qualitative approach, this study evaluates the effectiveness of the coretax application through in-depth interviews with users and secondary data analysis. The results show that coretax is able to simplify the tax reporting process for MSMEs through automation features, data integration, and comprehensive user guides. The application has a positive impact on increasing taxpayer compliance by reducing reporting errors and speeding up the filing process. However, this study also found several obstacles, such as low digital literacy among users and the need for additional training. Based on these findings, several strategic recommendations are provided to enhance the adoption and effectiveness of the coretax application in the future